Clinical efficacy and putative analgesic mechanism of heat-sensitive moxibustion for chronic nonspecific low back pain: a single-arm before-after study based on the brain-gut-immune axis - Yinfei Xie; Cheng Li (Frontiers in Integrative Neuroscience, 2026)
Background Chronic nonspecific low back pain (CNLBP) is one of the leading causes of disability worldwide. Growing evidence implicates brain-gut-immune axis dysregulation in the pathogenesis and perpetuation of chronic musculoskeletal pain. Heat-sensitive moxibustion (HSM), a refined form of traditional suspended moxibustion that targets heat-sensitized acupoints, has demonstrated preliminary analgesic efficacy, but its mechanisms through the brain-gut-immune axis remain unexplored. Objective To describe the clinical changes following HSM in patients with CNLBP and to explore its putative analgesic mechanism in relation to modulation of the brain-gut-immune axis, as assessed by nine serum biomarkers spanning neuroendocrine (β-endorphin, cortisol), intestinal barrier (lipopolysaccharide, D-lactate), gut-brain serotonergic signaling (5-hydroxytryptamine), and immune-inflammatory (interleukin-6, tumor necrosis factor-α, interleukin-10, high-sensitivity C-reactive protein) dimensions. Methods This single-arm, pre-post exploratory study enrolled 204 eligible CNLBP patients who received 20 sessions of HSM over four weeks. Primary outcomes were the Visual Analog Scale (VAS) and Oswestry Disability Index (ODI). Secondary outcomes included the Self-Rating Depression Scale (SDS), Self-Rating Anxiety Scale (SAS), and the nine-biomarker panel. Blood samples were collected at baseline and post-treatment. Paired t-tests or Wilcoxon signed-rank tests were used for pre-post comparisons. Treatment responders ( ≥ 50% VAS reduction) and non-responders were compared, and multivariable logistic regression was performed to identify predictors of treatment response. Results Of 204 enrolled patients, 186 completed the study (attrition rate, 8.8%). VAS scores decreased significantly after treatment (5.87 ± 1.38 vs. 2.21 ± 1.32; P < 0.001; Cohen’s d = 2.71), as did ODI scores (33.86 ± 11.24 vs. 18.42 ± 9.36; P < 0.001; d = 1.49). SDS and SAS scores also improved significantly ( P < 0.001). In the neuroendocrine dimension, β-endorphin increased and cortisol decreased ( P < 0.001). In the intestinal barrier dimension, LPS and D-lactate were significantly reduced ( P < 0.001). Serum 5-HT showed a trend toward elevation that did not reach significance after FDR correction (adjusted P = 0.094). In the immune-inflammatory dimension, IL-6, TNF-α, and hs-CRP decreased, while IL-10 increased ( P < 0.001). A total of 117 patients (62.9%) were classified as treatment responders. Compared with non-responders, responders showed significantly greater modulation in 8 of 9 biomarkers (all FDR-adjusted P < 0.05; 5-HT excepted). Multivariable logistic regression identified baseline heat-sensitization intensity, baseline VAS, and baseline LPS as independent predictors of treatment response (area under the curve = 0.828). Exploratory mediation analysis suggested that β-endorphin, IL-6, hs-CRP, LPS, and cortisol changes partially mediated the association between treatment dose and pain improvement. Conclusion Following HSM, CNLBP patients showed clinically meaningful pain relief and functional improvement. These uncontrolled observations are consistent with, but cannot confirm, a putative analgesic mechanism involving four-dimensional modulation of the brain-gut-immune axis: central endogenous opioid activation, intestinal barrier restoration, gut-brain serotonergic signaling regulation, and peripheral immune rebalancing. Baseline heat-sensitization intensity, pain severity, and intestinal permeability may serve as potential predictors of treatment response. As a single-arm study without a control group, these findings establish association and biological plausibility rather than causal efficacy, and warrant confirmation in a randomized controlled trial with a sham-moxibustion comparator.